Recent Advances in Understanding the Keys Factors Influencing Pressurized Liquid Extraction of Secondary Metabolites: A Comprehensive Review - Pauline Donn; Sepidar Seyyedi-Mansour; Franklin Chamorro; Paula Garcia-Oliveira; Javier Echave; Ana Perez-Vazquez; Paula Barciela; Lucia Cassani; Miguel Angel Prieto (Biology and Life Sciences Forum)
Pressurized liquid extraction (PLE) has become a pivotal technology for extracting secondary metabolites (e.g., phenolic compounds) from botanical sources, with implications spanning across pharmaceuticals, nutraceuticals, and functional foods. This communication provides an overview of recent advancements in understanding the key factors influencing the efficiency and selectivity of the PLE of these bioactive compounds. The optimization of PLE parameters, including pressure, temperature, and solvent characteristics, has been a focal point in recent research to enhance extraction yield and preserve the integrity of secondary metabolites. Investigations into the interaction of sample matrix properties, particle size, and solvent polarity have revealed nuanced effects on the extraction process, contributing valuable insights to developing targeted extraction protocols. Also, technological innovations, such as the utilization of green solvents and novel extraction techniques, are reshaping the landscape of PLE. Different studies exploring sustainable approaches not only enhance extraction efficiency but also align with the growing emphasis on environmentally friendly practices, paving the way for greener extraction processes. Collaborative efforts among researchers have led to a deeper understanding of the factors influencing PLE. Thus, this review highlights the recent progress in unraveling the complexities of the PLE of secondary metabolites, fostering a foundation for optimizing extraction methodologies and leveraging these bioactive compounds for diverse applications.